Bidirectional relationship between burnout and perceived work ability: Evidence from a two-wave study among teachers - Hlado, Petr; Lintner, Tomáš; Juhaňák, Libor; Harvankova, Klara (Applied psychology. Health and well-being, 2025)
Burnout and perceived work ability (PWA) are critical factors influencing teachers' professional well-being and effectiveness. The potential bidirectional relationship between these constructs remains underexplored, particularly in primary and lower secondary school teachers. This study examines the reciprocal relationship between burnout and PWA among teachers over time, using the job demands-resources (JD-R) model and the conservation of resources (COR) theory. A two-wave longitudinal study was conducted among 853 Czech primary and lower secondary school teachers. Data were collected via web-based questionnaires at two time points. Bayesian cross-lagged panel modeling (CLPM) was applied to analyze the bidirectional effects of burnout and PWA while controlling demographic variables. Burnout significantly predicted lower PWA, supporting the JD-R model's health impairment process. Contrary to expectations, higher PWA was associated with increased burnout, suggesting that PWA may not function as a protective factor in the teaching context, but rather as a risk factor increasing vulnerability to strain. Post hoc analyses indicated that burnout's detrimental influence on PWA emerged through several coherent facet-to-facet pathways, while in the reverse direction, only higher PWA in the teaching organization predicted later physical exhaustion. The study clarifies the directionality of associations between burnout and PWA, contributing to theory development and offering implications for interventions.
Keywords: Male; lidé středního věku; perceived work ability; Burnout, Professional; Humans; profesionální vyhoření; Middle Aged; Czech Republic; Česká republika; mužské pohlaví; Female; cross‐lagged panel modeling; učitelé; ženské pohlaví; conservation of resources theory; work ability; Adult; Longitudinal Studies; job demands‐resources model; longitudinální studie; lidé; dospělí; burnout; School Teachers